Síntese e estudo das propriedades térmicas e óticas de cristais líquidos contendo o heterociclo 1,2,4-oxadiazol - Cabral, Marília Gabriela Belarmino (2013)
To understand the structural factors that affect the formation of liquid crystal phase, two molecular series based on the structure of 3,5-diaryl-1,2,4-oxadiazole were synthesized and their thermal and optical prorperties investigated. The target compounds contain a long alkyl chain at one end and of the aromatic rigid portion, and a polar or polarizable group (NO2, F, Cl, Br, I) on the other side. These compounds had their chemical structures characterized by spectrometric methods (IR, 1H and 13C NMR). We performed an investigation of the optical properties in solution by UV-vis absorption and emission spectroscopy. Results indicated the main electronic transition involved is -*, revealing a direct conjugation of the 1,2,4-oxadiazole ring. Thermal stability and mesomorphic properties of the final products were studied by MOLP, DSC and X-ray diffraction. All final compounds exhibited liquid crystalline phases, in special SmA and N. Molecules containing NO2 terminal group showed a wide range of enantiotropic SmA phase (40 ºC). We found that the molecules possessing a halogen substituent only present monotropic liquid crystalline phases, that is, these phases can only be observed on cooling the samples, therefore they are naturally metastable. The results confirm the importance of a high dipole moment at one extremity of rigid core in generating lamellar nanostructures. The length of terminal alkyl chain was varied from 10 to 12 carbon atoms to study its influence in the phase stability. We found that the stability of lamellar nanostructures increased with the increasing length of the alkyl chain. In addition, the liquid crystalline phases for these compounds exhibit a spontaneous homeotropic alignment and a good thermal stability with temperature of decomposition above 320ºC